Mortality among Norwegian doctors 1960-2000 - Hem Erlend; Aasland Olaf G; Haldorsen Tor; Ekeberg Øivind (BMC, 2011)
Abstract Background To study the mortality pattern of Norwegian doctors, people in human service occupations, other graduates and the general population during the period 1960-2000 by decade, gender and age. The total number of deaths in the study population was 1 583 559. Methods Census data from 1960, 1970, 1980 and 1990 relating to education were linked to data on 14 main causes of death from Statistics Norway, followed up for two five-year periods after census, and analyzed as stratified incidence-rate data. Mortality rate ratios were computed as combined Mantel-Haenzel estimates for each sex, adjusting for both age and period when appropriate. Results The doctors had a lower mortality rate than the general population for all causes of death except suicide. The mortality rate ratios for other graduates and human service occupations were 0.7-0.8 compared with the general population. However, doctors have a higher mortality than other graduates. The lowest estimates of mortality for doctors were for endocrine, nutritional and metabolic diseases, diseases in the urogenital tract or genitalia, digestive diseases and sudden death, for which the numbers were nearly half of those for the general population. The differences in mortality between doctors and the general population increased during the periods. Conclusions Between 1960 and 2000 mortality for doctors converged towards the mortality for other university graduates and for people in human service occupations. However, there was a parallel increase in the gap between these groups and the rest of the population. The slightly higher mortality for doctors compared with mortality for other university graduates may be explained by the higher suicide rate for doctors.